Graduating from a Less Selective University during a Recession: Evidence from Mobility Report Cards and Employer Recruiting - Russell Weinstein (Institute of Labor Economics (IZA), 2021)
Using mobility report card data, I show graduates of less selective universities experience more adverse impacts of graduating in a recession. I highlight one mechanism: during recessions employers stop recruiting at less selective universities. Using a unique dataset of employer recruiting strategies for 65 prestigious firms, I show they are more likely to stop recruiting at universities that are less selective, smaller, farther, and have less affluent students. Firms also resume recruiting less quickly at less selective and farther campuses. Finally, losing access to prestigious firms while on campus is associated with an additional 13% decline in the 2014 income success rate.
Keywords: I26; I23; J23; J31; E32; 330; Great Recession; recent college graduates; employer recruiting; university selectivity